Temperature dependence on silver conductivity and adhesion performance between silver and flexible substrate - Omar, Ghazali; Mohd Yunos, Afiqah; Salim, Mohd Azli; Masripan, Nor Azmmi; Cosut, Bunyemin; Mohd Adnan, Ahmad Faris (Penerbit Akademia Baru, 2020)
Printed circuit board (PCB) is the main component in almost all electronic devices. The increase in the demand for PCB cause dramatically increases of E-waste. The improper discard practice of printed circuit board (PCB) leads to human health and environmental problems. Although the study had been done to improve the recycling process of E-waste, awareness from various parties needs more effort for this improved recycling process to successfully implement. Therefore, an alternative way by substitute the conventional PCB with the new flexible PCB can help eliminate these issues. The basic design of a flexible PCB consists of a flexible base and conductor. However, a key point during the developing of this new technology is the adhesion between the flexible base and conductor, which thermoplastic polyurethane (TPU) as the base, while silver as the conductor was used throughout this study. This paper presents the effect of temperature in improving adhesion between substrate and silver, and concurrently influence the electrical conductivity of silver conductor. In this study, the characterization of silver and substrate respected to temperature individually analysed, followed by the qualitative adhesion observation between silver and substrate was carried out through cross-cut test according to ASTM D3359-09. The silver was exposed to different curing temperatures exhibit lower sheet resistance when temperature increase. Meanwhile, the substrate exposed to a temperature higher than glass transition (Tg) increases improve the adhesion between silver and substrate.